Early farmers from across Europe directly descended from Neolithic Aegeans - Bradley, Daniel; Cassidy, Lara (My University, 2016)
One of the most enduring and widely debated questions in prehistoric archaeology concerns the origins of Europe’s earliest farmers: Were they the descendants of local hunter-gatherers, or did they migrate from southwestern Asia, where farming began? We recover genome-wide DNA sequences from early farmers on both the European and Asian sides of the Aegean to reveal an unbroken chain of ancestry leading from central and southwestern Europe back to Greece and northwestern Anatolia. Our study provides the coup de grâce to the notion that farming spread into and across Europe via the dissemination of ideas but without, or with only a limited, migration of people.
PUBLISHED
Cited By :8 Export Date: 13 January 2017
Keywords: genome-wide DNA sequences; genome-wide DNA sequences